Proceedings of SPE Unconventional Gas Conference 2010
DOI: 10.2523/131791-ms
|View full text |Cite
|
Sign up to set email alerts
|

Coalbed Methane: Current Evaluation Methods, Future Technical Challenges

Abstract: Coalbed methane (CBM) produced from subsurface coal deposits, has been produced commercially now for over 30 years in North America, and relatively recently in Australia, China and India. Historical challenges to predicting CBM well performance and long-term production have included: accurate estimation of gas-in-place (including quantification of in-situ adsorbed gas storage); estimation of initial fluid saturations (in saturated reservoirs) and mobile-water-in-place, estimation of the degree of under-saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Volumetric strain associated with gas sorption can also be measured in terms of the adsorbed gas volume at standard pressure and temperature. Experiments on the volumetric strain associated with methane and carbon dioxide adsorption have shown that the sorption-induced volumetric strain is approximately proportional to the volume of adsorbed gas (Cui and Bustin, 2005;Clarkson and Bustin, 2010), which also has been confirmed by Day et al (2010). The relationship is described as…”
Section: Coal Deformationmentioning
confidence: 68%
“…Volumetric strain associated with gas sorption can also be measured in terms of the adsorbed gas volume at standard pressure and temperature. Experiments on the volumetric strain associated with methane and carbon dioxide adsorption have shown that the sorption-induced volumetric strain is approximately proportional to the volume of adsorbed gas (Cui and Bustin, 2005;Clarkson and Bustin, 2010), which also has been confirmed by Day et al (2010). The relationship is described as…”
Section: Coal Deformationmentioning
confidence: 68%
“…According to the results of three experimental studies, the following important understanding of the influence of nanofluids on the pore structure of CBM reservoirs is obtained (1) The nanofluid treatment has a great impact on the SSA and pore diameter of the sample, especially on micropores, which is the key pore structure of CBM reservoirs. The maximum increase percentages of SSA, pore volume, and pore diameter are 228.12, 80.65, and 18.89%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the historical research on sorbed gas storage has focused on coalbed methane reservoirs; a recent summary of CBM gas content and sorption isotherm measurements, along with a discussion of uncertainties, was provided by Clarkson and Bustin (2010). Unlike most CBM plays, however, free-gas storage is often significant in shale gas reservoirs, and must be included in gas-inplace calculations (Ambrose et al, 2010).…”
Section: Gas Content and Adsorption Isothermsmentioning
confidence: 98%